2005
DOI: 10.1111/j.1365-3083.2005.01690.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma mycoides ssp. mycoides Biotype Small Colony‐Secreted Components Induce Apoptotic Cell Death in Bovine Leucocytes

Abstract: Contagious bovine pleuropneumonia, caused by Mycoplasma mycoides ssp. mycoides biotype small colony (MmmSC), is one of the most serious cattle diseases in Africa. Several observations suggested that MmmSC had evolved an efficient way to escape the bovine immune responses by triggering host-cell cytotoxicity. This study was implemented to determine whether the cytotoxic effect was due to apoptotic cell death. To that end, bovine blood cells were cultured for up to 3 days in the presence of viable or heat-killed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Live mycoplasmas have been detected in draining lymph nodes of MmmSC-infected animals [1,23] and have shown, recently, to induce apoptosis of lymphocytes in vitro [9]. In this study, impaired in vitro responses of animals developing acute CBPP was not due to an intrinsic lack of responsiveness of their lymphocytes as indicated by control experiments with the mitogen ConA (not shown).…”
Section: Secretion Of Ifn-γ Upon Stimulation Withmentioning
confidence: 53%
“…Live mycoplasmas have been detected in draining lymph nodes of MmmSC-infected animals [1,23] and have shown, recently, to induce apoptosis of lymphocytes in vitro [9]. In this study, impaired in vitro responses of animals developing acute CBPP was not due to an intrinsic lack of responsiveness of their lymphocytes as indicated by control experiments with the mitogen ConA (not shown).…”
Section: Secretion Of Ifn-γ Upon Stimulation Withmentioning
confidence: 53%
“…For Mycoplasma mycoides subsp. mycoides, it was previously shown that heat-inactivation results in impaired cytotoxicity (Dedieu et al, 2005). The main reason for this difference is that cell wall containing bacteria have components like lipoteichoic acid, peptidoglycans, or lipopolysaccharide that are recognized by the host immune system, whereas wall-less mycoplasmas do not have these classical virulence factors.…”
Section: Discussionmentioning
confidence: 98%
“…Peripheral blood mononuclear cells (PBMCs) were collected by density gradient centrifugation as previously described [53]. Bovine monocyte-derived dendritic cells (Bo-Mo-DC) were prepared from CD14-expressing cells using 40 ng/mL of both bovine recombinant IL-4 and GM-CSF as described in [54].…”
Section: Methodsmentioning
confidence: 99%